2002
DOI: 10.1089/08892220252779638
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immune Reconstitution in Antiretroviral Drug-Experienced Patients with Advanced HIV Disease

Abstract: Highly active antiretroviral therapy (HAART) of HIV disease is associated with effective virologic control, immune reconstitution, and clinical improvements. This study addresses the potential for improvements in lymphocyte phenotype and virologic responses of HIV-infected persons with extensive experience with dual nucleoside reverse transcriptase (NRTI) treatment and advanced HIV disease after a change to a potent antiretroviral therapy (NRTI + protease inhibitor). The majority of participants achieved virol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Although an early increase in both CD4 + T cells and memory CD4 + T lymphocytes can be noticed after 4 weeks of HAART, it has been shown to persist for 48 weeks [25]. Therefore, the timeline for IRIS occurrence might be longer than was previously proposed [38].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although an early increase in both CD4 + T cells and memory CD4 + T lymphocytes can be noticed after 4 weeks of HAART, it has been shown to persist for 48 weeks [25]. Therefore, the timeline for IRIS occurrence might be longer than was previously proposed [38].…”
Section: Discussionmentioning
confidence: 87%
“…Our group previously observed that Mycobacterium leprae-infected and HIV-infected patients who manifest borderline lepromatous leprosy and AIDS might shift to borderline tuberculoid disease after implementation of highly active antiretroviral therapy (HAART) and leprosy multidrug therapy, which suggests that, in some patients, granuloma formation might be altered by a HAART-induced increase in the CD4 + T cell count [23,24]. Another consequence of HAART-induced CD4 + T cell count improvement [25] is an apparent clinical deterioration that has been noted in a subgroup of patients, an immunopathological and inflammatory phenomenon known as immune reconstitution inflammatory syndrome (IRIS) [26]. Tuberculosis, Mycobacterium avium complex infection, cryptococcosis [27], cutaneous leishmaniasis [27,28], and other infectious and noninfectious diseases have been associated with IRIS [27].…”
mentioning
confidence: 99%
“…Decreases in activated CD4 and CD8 surface markers occur simultaneously and seem to be correlated with viral suppression [36]. Discordant responses among patients, such as increases in the CD4 + cell count despite the lack of suppression of viral replication, usually are differentiated by higher numbers of memory CD4 + cells and activated (CD38 + ) CD8 cells, as well as by a lower percentage of IL-2-producing CD4 + cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Among responders, the level of HIV RNA in plasma (viral load) falls by several orders of magnitude within the first 2–4 weeks of therapy, becoming “undetectable” (<50 copies HIV RNA/ml) within 16–24 weeks (fig 1). The CD4 count may return to normal with maximal virological suppression if HAART is given for a prolonged period of time,6 and immunological activity may largely be restored 7. Over the last decade, newer agents continue to be developed as additional viral and cellular host targets are identified, with 25 agents currently approved and on the market, with >10 more promising drugs in development (table 1).…”
Section: Historical Perspectivementioning
confidence: 99%